Controlling a 4 Degree of Freedom (4 DoF) Robot Arm with Hand Gestures Using Computer Vision Technology for Manufacturing Processes - Royyan Naufal Fauzan; Resa Pramudita (Universitas Sebelas Maret (UNS), 2024)
The increasing complexity of tasks in industrial environments requiring higher efficiency and precision is a major issue for industrial workers. To address these challenges, technology is needed to speed up the production process and improve quality. As part of artificial intelligence systems in industrial environments, robot arms are a solution that can be considered. The development of a robot arm that can be controlled with hand gestures through computer vision technology becomes a feasible solution. 4 Degree of Freedom (DoF) robot arm is chosen as the experimental platform for this research. The research method used in this study is research and development. Utilizing computer vision algorithms to track and detect user hand movements, the user can interact with the robot arm without using additional control devices. Hand object segmentation, feature extraction, and mapping to robot coordinates are parts of the hand gesture recognition process. The results of this research are expected to help develop a responsive and user-friendly robot arm control system. The system was tested under various usage conditions and achieved an average accuracy rate of 93%. With these research findings, it is expected to help industries develop new optimization solutions.